Evolution of Excitation–Inhibition Ratio in Cortical Cultures Exposed to Hypoxia - le Feber, Joost; Dummer, Anneloes; Hassink, Gerco C.; van Putten, Michel J. A. M.; Hofmeijer, Jeannette (Frontiers in Cellular Neuroscience, 2018)
In the core of a brain infarct, neuronal death occurs within minutes after loss of perfusion. In the penumbra, a surrounding area with some residual perfusion, neurons initially remain structurally intact, but hypoxia-induced synaptic failure impedes neuronal activity. Penumbral activity may recover or further deteriorate, reflecting cell death. Mechanisms leading to either outcome remain ill-understood, but may involve changes in the excitation to inhibition (E/I) ratio. The E/I ratio is determined by structural (relative densities of excitatory and inhibitory synapses) and functional factors (synaptic strengths). Clinical studies demonstrated excitability alterations in regions surrounding the infarct core. These may be related to structural E/I changes, but the effects of hypoxia /ischemia on structural connectivity have not yet been investigated, and the role of structural connectivity changes in excitability alterations remains unclear. We investigated the evolution of the structural E/I ratio and associated network excitability in cortical cultures exposed to severe hypoxia of varying duration. 6-12 hours of hypoxia reduced the total synaptic density. The In particular, the inhibitory synaptic density dropped significantly, further than the excitatory synaptic density, resulting in an elevated E/I ratio. Initially, this does not lead to increased excitability due to hypoxia-induced synaptic failure. Increased excitability becomes apparent upon reoxygenation after 6 or 12 hours, but not after 24 hours. After 24 hours of hypoxia, structural patterns of vGLUT stainings change. This possibly reflects disassembly of excitatory synapses, and may account for the irreversible reduction of activity and stimulus responses seen after 24 hours.